Nickel-catalyzed direct carboxylation of olefins with CO2: one-pot synthesis of α,β-unsaturated carboxylic acid salts - Huguet, Núria; Rominger, Frank; Hofmann, Peter (Chemistry - a European journal, 2014)
The nickel-catalyzed direct carboxylation of alkenes with the cheap and abundantly available C1 building block carbon dioxide (CO2) in the presence of a base has been achieved. The one-pot reaction allows for the direct and selective synthesis of a wide range of α,β-unsaturated carboxylates (TON>100, TOF up to 6 h−1, TON=turnover number, TOF=turnover frequency). Thus, it is possible, in one step, to synthesize sodium acrylate from ethylene, CO2, and a sodium salt. Acrylates are industrially important products, the synthesis of which has hitherto required multiple steps.